Up in STEM, Down in Business: Changing College Major Decisions with the Great Recession - Shimeng Liu; Weizeng Sun; John V. Winters (Institute of Labor Economics (IZA), 2017)
We use the American Community Survey (ACS) to investigate the extent to which college major decisions were affected during and after the Great Recession with special attention to business and STEM fields, as well as the heterogeneity by gender, race/ethnicity and combinations of race/ethnicity and gender. Several conclusions are reached. First, we see an overall increase in the frequency of STEM majors but a decrease in the frequency of business majors during and after the Great Recession. Second, the increase for STEM fields is spread across several detailed STEM fields, while the decrease in business majors is especially concentrated among finance and management. Third, we find strong heterogeneous effects by gender and race/ethnicity. Males are pushed away from business majors, while both males and females are pushed toward STEM majors; certain racial groups, such as white and Asian, seem to be affected more than others.
Keywords: I20; J24; 330; Great Recession; college major; business; finance; STEM